Role of Advertisement on Brand Choice of Tea - Shrestha, Neera (PRAGYAN A Peer Reviewed Multidisciplinary Journal, 2021)
This article attempts at exploring the role of advertisement on brand choice of tea. Most of the customers use tea every day in their life. It will be concentrated on influence of advertisement in brand choice of a tea. In other words, the study found out role of advertisement in brand choice. This research is carried out to see the different factors that consider the purchase decision of tea brand, participants of buying tea, knowledge about advertisement of tea, medium of advertisement, role of advertisement on brand choice and role of advertisement. For this, questionnaire survey of 60 tea users from different education and ethnic background are surveyed. By using simple descriptive method to analyze data, it is identified that they have all level of education from primary to master level, Tokla as first choice, duration of using current brand between less than one year to more than three years, advertisement is most important factor than price and quality, self purchase decider and buying participant. All of them have knowledge about advertisement and most of them use television as a medium of advertisement. The study finds that high role of advertisement on brand choice and advertisement is responsible to some extent in changing brand of tea as well.